Lesslie Newbigin and Edinburgh's Common Call: A Call for Humble Encounter and Faithful Witness. Issue 1 (22nd April 2019) - Robinson, Eric
Abstract: In a world where pluralism is the norm, interfaith encounter and dialogue are essential parts of the Christian experience. Lesslie Newbigin reflected extensively on a theological understanding of the Christian encounter with those of other faiths, emphasizing the importance of both a humble orientation toward God and others and a firm commitment to the uniqueness of Jesus Christ. This juxtaposition of humble witness and firm faith in interfaith encounter is also reflected in the Edinburgh 2010 mission conference's Common Call. This article will explore Newbigin's reflections on interfaith dialogue and consider their implications for the future of the ecumenical movement.